A bio-herbal medicinal remedies: M. Charantia Linn. A scope of characterization of medicinally evaluating antidiabetic compound. - U. WAHUL,; A.KADAM,; L.KAMBLE, (International Journal of Pharma and Bio Sciences, 2018)
As we aware diabetes is not only one kind of symptomatic disease but its occurrence spread through the various metabolic channels and hence raises other disorders. The prolonged symptoms of diabetes also cause the complications of eyesight, Night blindness, kidney failure, and other autoimmuno dysfunction including sexual dysfunction. In those symptomatic diseases various drugs are used to treat the diabetes such as biosimilar therapy including use of insulin and insulin analogues, oral hypoglycaemic agents and various other complementary medicines. As herbal remedies i.e. M charantia Linn. (Bitter Gourd) are commonly known as fruit vegetables. The Leaves, Seeds, Roots, Fruits and the stem part of the plants are medicinally used in different diseases. It is most effectively used to treat the acidic condition of gastrointestinal tract. M.charantia is also called the oxygen radical scavenger, which takes part into metabolic pathway. Due to the oxygen radical scavenging activity of GSH it directly expedites the ROS neutralization and the repair of ROS-induced damage which is important to neutralize the acidic condition of gastrointestinal tract. The present investigation was carried out to study the characterization of present antidiabetic compound having different solvent extract of M.charantia in various solvent system. The overall conclusion suggested that the extracted compound shows the antidiabetic and diuretic properties. The total unknown protein concentration was 21.01 µg/mL which is similar with standard antidiabetic drug and the slope consists of 0.0314 with the line of intercept 0.081, which has been elaborated in results and conclusion.